Solve the following system of equations, algebraically, by substitution.

y + 2x = 3

x = 3y + 5

y + 2x = 3

x = 3y + 5

**y + 2x = 3**

x = 3y + 5

x = 3y + 5

y + 2x = 3 {first equation}

y + 2(3y + 5) = 3 {substituted 3y + 5, in for x, into first equation}

y + 6y + 10 = 3 {used distributive property}

7y + 10 = 3 {combined like terms}

7y = -7 {subtracted 10 from each side}

y = -1 {divided each side by 7}

x = 3y + 5 {second equation}

x = 3(-1) + 5 {substituted -1, in for x, into second equation}

x = -3 + 5 {multiplied}

x = 2 {added}

**(2,-1)**is the solution to the system

Using the graphing calculator, you can see (2,-1) is the point of intersection of the two lines, as shown below: